The Effect Of English Central On Students’ Speaking Ability - Stevany Panjaitan; Safrida Lubis (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2026)
This study investigated the effect of the EnglishCentral platform on students' speaking ability, focusing on vocabulary accuracy and pronunciation accuracy among eighth-grade learners at SMP Negeri 17 Medan. A quantitative pre-experimental design was employed, with a pre-test and post-test control group design. Two groups were selected via cluster random sampling: a control group comprising 26 learners and an experimental group comprising 30 learners. Participants were instructed to deliver spoken responses lasting two to three minutes on opinion-based topics. In the experimental class, the EnglishCentral platform served as the primary instructional medium, providing authentic video-based content, native-speaker pronunciation models, and instant automated speech recognition feedback. Descriptive statistics, normality tests (Shapiro-Wilk), homogeneity tests (Levene), and paired-sample t-tests were conducted to analyze the data. The findings revealed that the experimental .group's mean vocabulary score rose from 66.77 (pre-test) to 73.77 (post-test), while pronunciation scores increased from 65.87 to 73.93. The paired samples t-test yielded a two-tailed significance value below 0.001 with a mean difference of - 6.18, confirming a statistically significant improvement. The control group's improvement, by contrast, was minimal (mean difference of 2.21). These outcomes confirm that integrating EnglishCentral into instruction produces measurable gains in vocabulary and pronunciation accuracy, particularly in the context of expressing and exchanging opinions